Electrical Stimulation of Afferent Pathways for the Suppression of Pathological Tremor - Dideriksen, Jakob L.; Laine, Christopher M.; Dosen, Strahinja; Muceli, Silvia; Rocon, Eduardo; Pons, José L.; Benito-Leon, Julian; Farina, Dario (Frontiers in Neuroscience, 2017)
Pathological tremors are involuntary oscillatory movements which cannot be fully attenuated using conventional treatments. For this reason, several studies have investigated the use of neuromuscular electrical stimulation for tremor suppression. In a recent study, however, we found that electrical stimulation below the motor threshold also suppressed tremor, indicating involvement of afferent pathways. In this study, we further explored this possibility by systematically investigating how tremor suppression by afferent stimulation depends on the stimulation settings. In this way, we aimed at identifying the optimal stimulation strategy, as well as to elucidate the underlying physiological mechanisms of tremor suppression. Stimulation strategies varying the stimulation intensity and pulse timing were tested in 9 tremor patients using either intramuscular or surface stimulation. Significant tremor suppression was observed in 6 patients (tremor suppression > 75% was observed in 3 patients) and the average optimal suppression level observed across all subjects was 52%. The efficiency for each stimulation setting, however, varied substantially across patients and it was not possible to identify a single set of stimulation parameters that yielded positive results in all patients. For example, tremor suppression was achieved both with stimulation delivered in an out-of-phase pattern with respect to the tremor, and with random timing of the stimulation. Overall, these results indicate that low-current stimulation of afferent fibers is a promising approach for tremor suppression, but that further research is required to identify how the effect can be maximized in the individual patient.